Complex reduction coefficient for a cylindrical electron beam with variable amplitude of the variable current component in the TWT - Chasnyk, V. I.; Strocovsky, Ya. N. (Technology and design in electronic equipment, 2013)
The conventional approach to calculating the space charge for the travelling-wave tube (TWT) with phase velocity jumps is to use the same values of the depression coefficient as the ones for homogeneous helical TWTs. However, if the variable component of the exciting current in the expressions for determining the reduction coefficient is changed in amplitude, then the reduction factor is a complex value. Perhaps the neglect of this fact can significantly affect the volume discharge calculated value, and hence the non-synchronization parameter, for those of its values, which are characteristic of the TWT with a phase velocity jump. In this paper, formulas has been obtained for computation of real and imaginary parts of the complex reduction coefficient for a cylindrical electrons beam with exponential variable amplitude of variable current component in the TWT. Influence of complex reduction coefficient on the parameters of the TWT operating in the linear mode is estimated. It is shown that taking into account the imaginary part of the reduction coefficient for linear operation of the TWT makes it possible to change the estimated amount of space charge 1.5 to 2 times, which in its turn has quite a strong effect on the formation of the initial conditions of the nonlinear mode and, subsequently, on the output characteristics of the TWT.